Impact of Human Papillomavirus (HPV) on Male and Female Fertility - Sara Chenafi-Adham; Oulfa Boussetta-Charfi; Sylvie Pillet; Thomas Bourlet (Pathogens)
Human papillomaviruses (HPVs) are responsible for the majority of sexually transmitted infections (STIs), some of which are oncogenic and can cause oropharyngeal or genital cancers. The HPV prevalence at the genital level varies according to the population studied but is higher in the seminal fluid of men suffering from idiopathic infertility than in the general population. The involvement of HPV in male infertility is supported by several studies suggesting that this virus can affect sperm quality by altering sperm DNA integrity, motility, number, viability, and morphology, and by inducing the production of anti-sperm antibodies (ASAs). HPVs may also have an impact on female fertility, mainly by increasing the risk of miscarriage and premature delivery and by altering the implantation of endometrial trophoblastic cells. In addition, an association with vaginal bacterial dysbiosis, notably involving Gardnerella vaginalis, or co-infection with an STI agent, serves as an aggravating factor. The aim of this review is to present current data on the potential role of HPVs in male and female infertility, along with data on infertility prevention and treatment strategies and the impact of vaccination in this context.